1996
DOI: 10.1128/mcb.16.8.4117
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Localization of Phosphatidylinositol 3-Kinase Is Sufficient To Activate Multiple Signal-Transducing Kinase Pathways

Abstract: Phosphatidylinositol (PI) 3-kinase is a cytoplasmic signaling molecule recruited to the membrane by activated growth factor receptors. The p85 subunit of PI 3-kinase links the catalytic p110 subunit to activated growth factor receptors and is required for enzymatic activity of p110. In this report, we describe the effects of expressing novel forms of p110 that are targeted to the membrane by either N-terminal myristoylation or C-terminal farnesylation. The expression of membrane-localized p110 is sufficient to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
431
4
1

Year Published

1998
1998
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(459 citation statements)
references
References 65 publications
22
431
4
1
Order By: Relevance
“…However, since inactivation of RalGDS has no e ect on cAMP response element (CRE) regulated gene expression (Miller et al, 1997), it is unlikely that this pathway plays a major role in the expression of the thyroid di erentiated phenotype. Another Ras e ector that could be potentially involved in thyrocyte differentiation control and transformation is PI3-K (Klippel et al, 1996;Rodriguez-Viciana et al, 1994). In Âźbroblasts dominant-negative forms of PI3-K are able to inhibit signiÂźcantly Ras transformation (Rodriguez-Viciana et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…However, since inactivation of RalGDS has no e ect on cAMP response element (CRE) regulated gene expression (Miller et al, 1997), it is unlikely that this pathway plays a major role in the expression of the thyroid di erentiated phenotype. Another Ras e ector that could be potentially involved in thyrocyte differentiation control and transformation is PI3-K (Klippel et al, 1996;Rodriguez-Viciana et al, 1994). In Âźbroblasts dominant-negative forms of PI3-K are able to inhibit signiÂźcantly Ras transformation (Rodriguez-Viciana et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors such as EGF have been shown to activate the JNK pathway through PI3K (Logan et al, 1997). Overexpression of PI3K catalytic subunit (p110) can lead to Rac activation (Klippel et al, 1996;Minden et al, 1995;Minden and Karin, 1997) and its expression in COS cells was shown to induce activation of JNK (Rei et al, 1996). Taken together these data suggest that the PI3K activated pathway could be similarly involved in coupling Rac signalling to stress activated kinases.…”
Section: Introductionmentioning
confidence: 86%
“…Akt, one of these kinases, is notable in that it is a direct target of the phosphatidylinositol 3-kinase (PI3-K) Kohn et al, 1995;Andjelkovic et al, 1996;Burgering and Co er, 1995;Klippel et al, 1996;Datta et al, 1996), and as such it plays an important role in regulating many cellular functions that depend on the activity of this enzyme (Kapeller and Cantley, 1994). The activation of Akt by PI3-K was determined by experiments mapping the pathway that regulates Akt following stimulation by a variety of growth factors Kohn et al, 1995;Burgering and Co er, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The activation of Akt by PI3-K was determined by experiments mapping the pathway that regulates Akt following stimulation by a variety of growth factors Kohn et al, 1995;Burgering and Co er, 1995). This was conÂźrmed by studies showing that the activated catalytic subunit of the PI3-K is su cient to activate Akt in the absence of growth factor stimulation (Klippel et al, 1996;Datta et al, 1996). Our early studies, identifying Akt as a direct target of the PI3-K, showed that an Akt immunoprecipitate from lysates of serum-starved NIH3T3 cells was activated when incubated with D3 phosphorylated phosphoinositides (D3 PPIs) .…”
Section: Introductionmentioning
confidence: 99%